Kemampuan Representasi Matematis Bilangan Pecahan Pada Siswa Kelas III SD dengan Menggunakan Model Project Based Learning - Restu, Naila Kurnia; Ruqoyyah, Siti; Samsudin, Asep (IKIP Siliwangi, 2020)
This study attempts to analyse scenarios and implementation, the teachers and students, as well as the difficulties experienced by students in complete the task. The representation of a mathematical very important applied at the primary school 3rd class, due to find way of thinking students in conveying the idea of creating mathematical abstract to concrete. Through a project based learning (PjBL ), they can make some simple floating material concept into something concrete and can be used to reduce a learning disability and maths both more interactive and attractive. Descriptive qualitative use of this research. The scenarios and point to the findings from the students can learn more active teacher lessons learned by means of concrete using media and social interaction between teachers or friends. A very good teachers and students. The difficulties experienced by students in complete a task the floating a representation of a mathematical equation of the make or model of mathematical representations received and devise story to suit a representation served. Based on the results of research and of the discussion on this research, it can be deduced that there is the representation of the student mathematical 3rd class especially on math material floating PjBL after enactment of the model. Keywords: Representation Mathematical, Project Based Learning Model.